The standardization and certification procedures of cryogenic equipmentin Kazakhstan - Shinbayeva, A.; Drobyshev, A. (Recent Contributions to Physics, 2015)
Creation of the Common Economic Space and functioning within the framework of EurAsEC of industrial enterprises requires forming a common base of normative documents to the Member States. Considering the whole increasing role of the cryogenic technologies in the industrial development of the world’s leading powers, it is necessary to carry out the appropriate set of activities of normative ensuringthis occupation.
Keywords: cryogenic equipment; regulations; standards.